Plasma Sirt-1 Level in Various Frailty Degree in Elderly Outpatients at Prof. Chairudin P. Lubis Hospital, Medan - Fadhilah Hayati; Dedi Ardinata; Nuraiza Meutia; Ririe Fachrina Malisie; Muhammad Ichwan (Talenta Publisher, 2023)
Frailty is a physical aging syndrome characterized by health vulnerability. Diagnosis is established incorrectly based on three or more of the five criteria: weakness, decreased walking speed, fatigue, decreased physical activity, and weight loss. Sirtuin 1 plays a role in weakness, particularly in the elderly, acting as a protective factor during weakness, and its activation could provide a novel therapeutic approach. However, research in this area is still very limited. A cross-sectional method with observation or measurement of study subjects was employed in this research, involving a total of 118 elderly subjects selected through non-probability sampling. Pearson correlation test indicates a relationship between the polymorphism genotype (rs2273773) in the SIRT1 gene and the frailty scale (p-value < 0.05), while no relationship was found between plasma SIRT1 levels and the frailty scale (p-value > 0.05). Furthermore, the F-test reveals a significant simultaneous relationship between the polymorphism genotype (rs2273773) and plasma SIRT1 levels with frailty (p-value < 0.05).